KUALITAS PEMBERIAN SUSU ETAWA TERHADAP PENINGKATAN BERAT BADAN PADA PASIEN TB PARU DAN TB MDR - Herlia Sumardha Nasution; Purnama Handayani; Rizki Noviyanti Harahap (Universitas Prima Indonesia, 2021)
Pulmonary TB is an infection caused by mycobacterium tuberculosis. These bacteria infect the lungs. Patients usually experience symptoms of a prolonged cough to bloody cough, decreased appetite, weight loss. This study aims to determine the effect of giving etawa milk on weight gain in pulmonary tuberculosis patients at Tanjung Rejo Public Health Center. This study used a research design with a quasi-experimental approach and one group pre and post-test design. The population was in this study was pulmonary tuberculosis patients. until as many as 30 people. The results of patients with pulmonary tuberculosis, the majority of pre-milk etawa, the weight of 45 kg pulmonary tuberculosis patients were 5 people (33.5%) and weight of 43 kg multi-drug resistant patients were 4 people (26.7%). The results of patients with pulmonary tuberculosis, the majority of post milk etawa, the weight of 47 kg pulmonary tuberculosis patients were 7 people (46.7%) and weight of 45 kg multi-drug resistant patients were 5 people (33.3%). Pulmonary tuberculosis patients (0.049) and multi-drug resistant patients (0.047) there is an effect of giving etawa milk on weight gain in pulmonary tuberculosis and multi-drug resistant patients at the Tanjung Rejo Public Health Center, Deli Serdang Regency, 2020. The results showed that giving etawa milk can improve appetite which results in body weight. It is recommended for patients to participate in practicing the efficacy of etawa milk for the traditional treatment of pulmonary TB disease.